Evaluation of the Effect of Wet Cupping on hematological parameters in a sample of Libyan Adults - Eman Abdulwahed; Khaled Elbaruni; Esraa Hassan; Maram Habli; Ahmed Atia (Khalij-Libya Journal of Dental and Medical Research, 2025)
Wet cupping is an ancient procedure used to treat and prevent various systemic diseases by removing blood from the body. This study aimed to analyze the impact of wet cupping on complete blood count (CBC) parameters in adults aged between 22 and 50 years. This study was conducted from June to August 2023 and involved 50 participants who were interested in undergoing wet cupping. Of these participants, 21 were male and 29 were female. Blood samples were taken before their first cupping session and again two weeks after the session. The collected blood samples were analyzed using a hematology analyzer (Sysmex-XP 300) to perform a complete blood count (CBC) analysis. There were no significant differences in the mean levels of WBC, RBC, MCV, MCH, MCHC, and PLT between the pre-cupping and post-cupping samples. However, the hemoglobin and hematocrit levels significantly decreased in the post-cupping samples compared to the pre-cupping samples (P=0.009 and P=0.004, respectively). In conclusion, based on the study’s findings, wet cupping did not cause any significant changes in the RBC, WBC, MCV, MCH, MCHC, and PLT levels, but there were significant decreases in the HGB and HCT levels. الحجامة الرطبة هي إجراء قديم يستخدم لعلاج والوقاية من الأمراض الجهازية المختلفة عن طريق إزالة الدم من الجسم. هدفت هذه الدراسة إلى تحليل تأثير الحجامة الرطبة على معايير تعداد الدم الكامل لدى البالغين الذين تتراوح أعمارهم بين 22 و 50 عامًا. أجريت هذه الدراسة من يونيو إلى أغسطس 2023 وشارك فيها 50 مشاركًا مهتمين بالخضوع للحجامة الرطبة. من بين هؤلاء المشاركين، كان 21 من الذكور و 29 من الإناث. تم أخذ عينات الدم قبل جلسة الحجامة الأولى ومرة ​​أخرى بعد أسبوعين من الجلسة. تم تحليل عينات الدم التي تم جمعها باستخدام جهاز تحليل أمراض الدم لإجراء تحليل تعداد الدم الكامل. لم تكن هناك فروق ذات دلالة إحصائية في متوسط ​​مستويات خلايا الدم الحمراء، وخلايا الدم البيضاء، وحجم خلايا الدم الوسطى، ومستوى تركيز الماكرو في الدم، ومستوى تركيز الماكرو في الدم، ومستوى الصفائح الدموية. بين عينات ما قبل الحجامة وما بعدها. مع ذلك، انخفضت مستويات الهيموغلوبين والهيماتوكريت بشكل ملحوظ في عينات ما بعد الحجامة مقارنةً بعينات ما قبل الحجامة P=0.009 وP=0.004 على التوالي . في الختام، وبناءً على نتائج الدراسة، لم تُحدث الحجامة الرطبة أي تغيرات ملحوظة في مستويات خلايا الدم الحمراء، وخلايا الدم البيضاء، وحجم خلايا الدم الوسطى، ومستوى تركيز الماكرو في الدم، ومستوى تركيز الماكرو في الدم، ومستوى الصفائح الدموية، ولكن كان هناك انخفاض ملحوظ في مستويات الهيموغلوبين ومستوى الهيماتوكريت